The Evidence Base of Czech Health Policy - Jan Klusáček; Marie Klusáčková (Central European Journal of Public Policy, 2012)
The article deals with the evidence base of health policy in the Czech Republic. It focuses on articles published in peer-reviewed scholarly journals. It builds on a quantitative analysis of articles published between 2005 and 2010 in scholarly journals in the fields of social science, management and administration, public health and other relevant fields. The main finding is that almost half of the 161 articles with potential use for health policy were published in a single journal, Zdravotnictví v České republice. A part of the articles that can be utilized by health policy was published in journals focusing on public health and nursing; those, however, mostly did not contain analyses of or recommendations for health policy. Almost no articles with health policy relevance came out in social science (economy, political science, sociology) journals published in the Czech Republic. Authors of health-policy-relevant articles worked at a broad spectrum of institutions.